Pentingnya Akuntansi Syariah di Era Modern - Artika Dewi Putri; Rayyan Firdaus (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The importance of Islamic accounting in this modern era is increasingly relevant, especially in preventing unexpected practices such as fraud, dishonesty and other abuses in the world of accounting. Specifically, this paper analyzes the values of Islamic principles applied in the accounting process to avoid the emergence of these practices. The methodology used in this research is descriptive analysis, where the author elaborates on the main elements of Islamic principles applied in accounting. Furthermore, this paper attempts to differentiate clearly between the basic values underlying Islamic accounting and conventional accounting.The comparative findings between the two systems show that Islamic values, such as honesty, fairness and truth—which are important principles in Islamic accounting—have a deeper meaning when compared to the same values in conventional accounting. The firm application of Islamic principles in accounting can clearly reduce fraudulent practices and other unexpected activities. Apart from that, this also contributes to increasing social welfare for stakeholders, because Islam encourages society to provide maximum benefits to other communities.The practical implication of this research is the need to redefine values in conventional modern accounting, so that stakeholders can obtain greater benefits and reduce potential losses for society. The value of financial reporting should not only reflect current conditions, but also provide solutions that can improve the welfare of stakeholders.